Unravelling the effect of charge dynamics at the plasmonic metal/semiconductor interface for CO2 photoreduction. Issue 1 (December 2018) - Collado, Laura; Reynal, Anna; Fresno, Fernando; Barawi, Mariam; Escudero, Carlos; Perez-Dieste, Virginia; Coronado, Juan; Serrano, David; Durrant, James; Peña O'Shea, Víctor
Abstract Sunlight plays a critical role in the development of emerging sustainable energy conversion and storage technologies. Light-induced CO2 reduction by artificial photosynthesis is one of the cornerstones to produce renewable fuels and environmentally friendly chemicals. Interface interactions between plasmonic metal nanoparticles and semiconductors exhibit improved photoactivities under a wide range of the solar spectrum. However, the photo-induced charge transfer processes and their influence on photocatalysis with these materials are still under debate, mainly due to the complexity of the involved routes occurring at different timescales. Here, we use a combination of advanced in situ and time-resolved spectroscopies covering different timescales, combined with theoretical calculations, to unravel the overall mechanism of photocatalytic CO2 reduction by Ag/TiO2 catalysts. Our findings provide evidence of the key factors determining the enhancement of photoactivity under ultraviolet and visible irradiation, which have important implications for the design of solar energy conversion materials. Light-driven CO2 reduction provides a way to limit greenhouse gas concentrations, but understanding how materials accomplish this transformation is challenging. Here, authors examine the reaction over plasmonic silver-titanium dioxide using time-resolved, in situ techniques to follow the mechanism.